Tootsie - Grusin, Dave 1934- (<<The>> Criterion Collection, 2014)
"In "Tootsie", Michael Dorsey lands the role of a lifetime as did the actor playing him, Dustin Hoffman. This multilayered comedy from Sydney Pollack follows the elaborate deception of a down-on-his-luck New York actor who poses as a woman to get a soap opera gig; while "Dorothy Michaels" skyrockets to fame, Michael finds himself learning to be a better man. [...] "Tootsie" is a funny, cutting, and poignant film from an American moment defined by shifting social and sexual identities." [criterion.com]
Aspect ratio 2.40:1. - New 4K digital restoration
Orig.: USA 1982
Enth. audio commentary featuring director Sydney Pollack ; new interviews with actor Dustin Hoffman and comedy writer Phil Rosenthal ; interview with Dorothy Michaels by film critic Gene Shalit ; the making of "Tootsie" (1982) and "A better man: the making of 'Tootsie'" (2007), two documentaries featuring interviews with cast and crew ; screen and wardrobe test footage ; deleted scenes and trailers ; an essay by critic Michael Sragow